Prehistory of Bangladesh in the Light of Recent Discovery - Badal, Bakhtiar Uddin; Md. Sadequzzaman; Khatun , Sumaia (CenRaPS Journal of Social Sciences, 2024)
Bangladesh has deep historical roots, with a significant concentration of prehistoric evidence discovered primarily at the Lalmai Hill range in Cumilla district and Chaklapunji in Habiganj district. This study focuses on the Lalmai Hill range in Cumilla, which comprises multiple sites that have garnered considerable attention due to their rich prehistoric heritage. While previous investigations focused on the southern part, covering a length of 16.53 km and a width of 1 km to 2.5 km, this study aimed to explore the entire hill range with the objective of uncovering new signs of prehistoric activities and digitally documenting them. Intrusive surface surveys were conducted in an unsystematic manner due to the challenging hilly terrain, and samples were collected without following a predetermined sampling strategy. The findings reveal the discovery of four new sites in the southern region, where sixty-one Stone Age tools were unearthed. The results show that the tool assemblages consist of two major categories with six different varieties based on their typology. Detailed examination of the physical attributes of the tools primarily reveals controlled knapping techniques applied to remove flakes and manufacture the tools. The presence of fossil wood and the absence of fossil wooden tools in the northern and middle sections of the hill range suggest that the southern part offered favorable environmental resources for shelter to prehistoric migrants. Additionally, the exposed fossil woods, which served as suitable raw material, are prominent features of the Dupi Tila formation, dating back to the Plio-Pleistocene epoch. The study underscores the importance of continued investigation and excavation to unravel the intricate signs of prehistoric culture within this archaeological landscape.